USING THERMOPLASTIC BASE MATERIALS IN THE CLINIC OF ORTHOPEDIC DENTISTRY IN THE TREATMENT OF PATIENTS WITH COMPLETE TOOTH LOSS - V.S. Kuz (Український стоматологічний альманах)
Background. Fabrication of high-quality removable orthopedic structures is one of the most important and still unsolved problems in the clinic of prosthetic dentistry. In order to solve this problem, in recent years, new basic dental materials have been developed and researched. Nowadays, orthopedic dentists are increasingly using acrylic-free thermoplastic base materials. They provide opportunities for the treatment of patients, contributing to the improvement of comfort, functionality and aesthetics of complete dentures.